EVALUASI PROGRAM PEMBERDAYAAN PENYANDANG DISABILITAS DALAM MEWUJUDKAN KEMANDIRIAN EKONOMI KELUARGA DIDESA TAMAN AYU KABUPATEN LOMBOK BARAT - M. Arief Rizka; Aulia Ramani Dewi; Suharyani (Comm-Edu (Community Education Journal), 2026)
This study aims to evaluate the implementation of the empowerment program for persons whit disabilities in achieving family economic independence in taman ayu village, gerung district, west lombok regency. The study employed a descriptive quantitative approach using the CIPP evaluation model (context, input, process, product) developed by stufflebeam. The research subjects consisted of 15 participants of the empowerment program selected using the purposive sampling technique. Data were collected throught questionneires, observations, and documentations, while data analysis was carried out using the likert scale percentage formula.The results showed that the empowerment program for persons with disabilities in Taman Ayu Village was higly effective, with an average evaluation score of 93.8%. in detail, the context aspect obtained a score of 93.1% the input aspect 93.7%, the process aspect 94.0% and product aspect 94.3%. these findings indicate that the implementation of the program has met the needs of persons with disabilities, supported by adequate resources and facilities, and has successfully improved perticipantas’ skills, knowledge, and economic independence. Therefore, the empowerment program for persons with disabilities in taman ayu village can be considered successful in helping achieve family economic independence. However, further follow-up is needed in the form of continued mentoring and access to business capital support to make the program’s outcomes more optimal and sustainabel.